Número completo - Antolinez Franco, Johan Stephen; Sánchez Lemus, Angela Cristina; Hernández, Jairo Andrés (Ciudad Paz-ando, 2017)
Volumen 10, número 2 del año 2017 - Diez años comprometidos con la construcción de paz